Mapping Instructional Design Models in Educational Product Development: A PRISMA-Based Qualitative Meta-Analysis - Sholeh Hidayat; Fira Wibawanti; Lestari Aziza; Mulyasaroh Mulyasaroh; Putri Neta Nababan; Fahra Putri Ardita; Suci Mega Dian Sari; Firman Fathulrohman; Atin Fatimah (LPPM Institut Pendidikan Nusantara Global, 2026)
The rapid growth of educational technology has increased the need for appropriate instructional design models in educational product research and development (R&D). This qualitative meta-analysis maps the use of five widely adopted models–ADDIE, Kemp, Dick and Carey, Borg and Gall, and Gagné–in educational product development studies published from 2020 to 2025. Scopus-indexed articles were used as the data source because they provide peer-reviewed publications, internationally comparable metadata, and sufficient bibliographic consistency for transparent PRISMA-based screening. The study identified 335 records and retained 240 articles that met the inclusion criteria. Data were analyzed through narrative synthesis by coding the instructional design model, product type, research method, author characteristics, and implementation pattern. The findings show that ADDIE and Borg and Gall are the most frequently used models, especially in R&D studies and in the development of digital learning media, learning resources, and instructional products requiring staged validation. Dick and Carey, Gagné, and Kemp appear less frequently and are generally applied in more specific instructional contexts. These findings indicate that model selection is shaped by research objectives, product scale, development complexity, and reporting demands. The study contributes a comparative reference for selecting instructional design models in educational product development.